Neural Plasticity of Extinction: Relations with Anxiety and Extinction Retention - (:unkn) unknown (My University, 2016)
ABSTRACT NEURAL PLASTICITY OF EXTINCTION LEARNING: RELATIONS WITH ANXIETY AND EXTINCTION RETENTION by Emily L. Belleau The University of Wisconsin-Milwaukee, 2016 Under the Supervision of Associate Professor Christine Larson Anxiety is a significant public health problem characterized by substantial psychological, physical, and economic burden. A key feature of anxiety is the inability to regulate fear. Aberrant extinction of conditioned fear is one prominent model of the etiology of anxiety disorders. Previous studies have shown that the neural circuitry underlying anxiety pathology overlaps with that mediating fear extinction learning. Recently, more precise pathways supporting the expression (CMA-aMCC) and inhibition (BLA-vmPFC) of conditioned fear have been identified, and dysfunction in these pathways has been linked with anxiety. However, this work has focused on examining these pathways at one point in time, outside of the context of learning, and no one has examined plastic changes in functional activity before and after extinction learning. In addition, no one has applied this inquiry to individual differences in anxiety and extinction retention. This gap in knowledge is a problem because deficits in extinction-induced neural plasticity may be a substantial contributing factor to sustained fear responses in anxiety. The aim of this project was to examine changes in the strength of CMA-aMCC and BLA-vmPFC pathways from before to after extinction learning and how this is related to anxiety and retention of extinction. In a more exploratory fashion, I investigated the degree to which extinction-related plasticity varies as a function of white matter integrity within these pathways. Our results indicated that extinction learning is associated with enhanced plasticity in fear inhibition circuits (BLA-vmPFC and CMA-vmPFC). Plasticity in these circuits appears to be intact in high anxious individuals. However, trait anxiety was positively associated with strengthened connectivity in a fear expression pathway (BLA-aMCC). Enhanced plasticity within a fear expression circuit likely contributes to fear inhibition problems, a core feature of anxiety problems.
Keywords: Anxiety; Extinction Learning; Extinction Retention; Fear; Fear Conditioning; Neural Plasticity